Clinical investigation on nebulized human umbilical cord MSC-derived extracellular vesicles for pulmonary fibrosis treatment - Meng Li; Huaping Huang; Xiaofei Wei; Huajuan Li; Jun Li; Bingchen Xie; Yuze Yang; Xingyue Fang; Lei Wang; Xiaona Zhang; Heyu Wang; Mengdi Li; et al. (Signal Transduction and Targeted Therapy, 2025)
Abstract Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are recognized as a promising strategy for cell-free therapy, however, their therapeutic role in pulmonary fibrosis remains unrevealed. Here, we report the safety and efficacy of MSC-EVs from human umbilical cord (hUCMSC-EVs) evaluated in mouse models and pulmonary fibrosis patients. We established a rigorous system to produce high-quality of hUCMSC-EVs, characterized by miRNA, protein, and metabolite profiles. When administered via nebulization, hUCMSC-EVs predominantly accumulated in murine lungs and ameliorated bleomycin-induced pulmonary fibrosis, with increased survival rate (from 20% to 80%), restored lung volume, and attenuated injury severity accompanied by elevated oxyhemoglobin saturation and improved pulmonary function evaluations. We performed a phase l clinical trial involving twenty-four patients in a randomized, single-blind, and placebo-controlled study to treat pulmonary fibrosis (MR-46-22-004531, ChiCTR2300075466). All participants tolerated the nebulized hUCMSC-EVs well, with no serious adverse events. Patients receiving the combined therapy of nebulized hUCMSC-EVs and routine treatment demonstrated significant improvements in both lung function indices (forced vital capacity and maximal voluntary ventilation) and respiratory health status (as measured by the Saint George’s Respiratory Questionnaire and Leicester Cough Questionnaire. Overall, patients upon the additional therapy with nebulized hUCMSC-EVs gained significant benefits compared with those accepted only routine treatment. Remarkably, two patients with advanced post-inflammatory pulmonary fibrosis exhibited clinically significant regression on serial CT scans after hUCMSC-EVs therapy. These findings suggest that nebulized hUCMSC-EVs could be used as a promising therapeutic strategy for treating pulmonary fibrosis diseases.